Alternative Imaging Modalities in Ischemic Heart Failure (AIMI-HF) IMAGE HF Project I-A: study protocol for a randomized controlled trial - O’Meara, Eileen; Mielniczuk, Lisa M; Wells, George A; deKemp, Robert A; Klein, Ran; Coyle, Doug; Mc Ardle, Brian; Paterson, Ian; White, James A; Arnold, Malcolm; Friedrich, Matthias G; Larose, Eric; et al. (Université d'Ottawa | University of Ottawa, 2013)
Abstract Background Ischemic heart disease (IHD) is the most common cause of heart failure (HF); however, the role of revascularization in these patients is still unclear. Consensus on proper use of cardiac imaging to help determine which candidates should be considered for revascularization has been hindered by the absence of clinical studies that objectively and prospectively compare the prognostic information of each test obtained using both standard and advanced imaging. Methods/Design This paper describes the design and methods to be used in the Alternative Imaging Modalities in Ischemic Heart Failure (AIMI-HF) multi-center trial. The primary objective is to compare the effect of HF imaging strategies on the composite clinical endpoint of cardiac death, myocardial infarction (MI), cardiac arrest and re-hospitalization for cardiac causes. In AIMI-HF, patients with HF of ischemic etiology (n = 1,261) will follow HF imaging strategy algorithms according to the question(s) asked by the physicians (for example, Is there ischemia and/or viability?), in agreement with local practices. Patients will be randomized to either standard (SPECT, Single photon emission computed tomography) imaging modalities for ischemia and/or viability or advanced imaging modalities: cardiac magnetic resonance imaging (CMR) or positron emission tomography (PET). In addition, eligible and consenting patients who could not be randomized, but were allocated to standard or advanced imaging based on clinical decisions, will be included in a registry. Discussion AIMI-HF will be the largest randomized trial evaluating the role of standard and advanced imaging modalities in the management of ischemic cardiomyopathy and heart failure. This trial will complement the results of the Surgical Treatment for Ischemic Heart Failure (STICH) viability substudy and the PET and Recovery Following Revascularization (PARR-2) trial. The results will provide policy makers with data to support (or not) further investment in and wider dissemination of alternative ‘advanced’ imaging technologies. Trial registration NCT01288560